Compound weights exercises to develop your endurance and influence in the skill of handling receipt ending pectoral hands of the young basketball players game - Sami, Luay (Journal of Physical Education, 2013)
The importance of the research problem in the development of vehicle weights exercises to develop strength and bearing impact statement in the performance of the skill of receipt ending handling thoracic hands of young basketball players.The research objectives are the numbers of compound weights exercises for basketball players for young people and find out the impact of these exercises in the development of bearing strengths of the sample, as well as their impact on the performance of the skill of receipt ending handling thoracic hands.The researcher used the experimental nature of the problem of suitability, and the research sample consisted of players Adhamiya Sports Club for youth basketball ages (16-17) years for season (2011-2012), and numbered (8) players. After obtaining the results, statistically treated, the researcher suggested some of the conclusions and recommendations.Conclusions:- The training exercises using the compound weights helped to develop the work of the neuromuscular system, which in turn impacted on the effectiveness of performance skills .- The training exercises using the compound weights helped to develop the strength to bear the muscles of the arms and legs of the players who trained him. Recommendations:- Rely on curriculum exercises using weights compound capacity when special physical training. - Need to have training exercises using weights in a manner similar compound performance skills to include the training of skilled working muscles